A simulation study of Top and Bottom Counting Detectors in ISS-CREAM experiment for cosmic ray electron physics. Issue 10 (15th November 2018) - Park, J.M.; Amare, Y.; Anderson, T.; Angelaszek, D.; Anthony, N.; Arnold, H.; Choi, G.H.; Copley, M.; Coutu, S.; Derome, L.; Ebongue, C.; Eraud, L.; et al.
Abstract: The Cosmic Ray Energetics and Mass experiment at the International Space Station (ISS-CREAM) is developed for studying the origin, acceleration and propagation mechanism of high energy cosmic rays. The Top and Bottom Counting Detectors (TCD/BCD), sub-detectors of the ISS-CREAM instrument, are developed for electron/ γ -ray physics. The TCD/BCD help distinguish electrons from protons by comparing the hit and shower width distributions for electrons and protons. The e/p separation capability of the TCD/BCD is studied by using the GEANT3 simulation package, and optimal parameters for the e/p separation are obtained.